(untitled) (Journal of Environmental Science and Natural Resources, 2016)
Effect of NaCl on nutrient uptake was observed from a phytodesalination study by three abundantly grown sodium accumulating halophytes namely, Kalmilata (Ipomoea aquatica), Malancha (Alternanthera philoxeroides) and Kesordam (Ludwigia adscendens L.). A 45 days hydroponic experiment was conducted with these halophytes treated with 0, 3, 5 and 7 dS m-1 salt added from the sodium chloride (NaCl). After analyzing water and plant parts, it was observed that potassium (K) and phosphorus (P) uptake were increased by plants and less effect on calcium (Ca), magnesium (Mg) and chloride (Cl-) uptake due to added NaCl. Simultaneously the biomass content increased in Kalmilata rather than Malancha and Kesordam. So non-altered nutritional status makes these halophytes suitable for vegetable, fodder and forages use after phytodesalination of saline water. J. Environ. Sci. & Natural Resources, 9(1): 9-15 2016